Development of a Questionnaire Evaluating the Knowledge, Attitude, and Practice on Geriatric Dermatology among Elderly Caregivers - Shannaz Nadia Yusharyahya; Valdi Ven Japranata; Christine Lieana; Lili Legiawati; Rinadewi Astriningrum; Wresti Indriatmi (Faculty of Medicine Universitas Indonesia, 2022)
Information concerning the extent of knowledge, attitude, and practice of elderly caregivers about dermatological care are still limited. This present study aimed to develop a tool with decent validity and reliability to delineate such profiles. A questionnaire was designed by geriatric dermatology experts, followed by content validation and reliability tests using Aiken’s V coefficient, Kuder-Richardson Formula 20 (KR-20) or Cronbach’s α, and Pearson’s correlation. The developed instrument was tested on elderly caregivers, before and after education. Obtained data were analyzed using appropriate inferential statistics. We found that the Aiken’s V coefficient for each item was ≥0.70; KR-20 in knowledge section was 0.81; Cronbach’s α in attitude and practice section were 0.81 and 0.80, respectively; and Pearson’s correlation in all sections was above 0.80. Significant disparities were observed in the initial knowledge (p=0.005) and attitude (p=0.020) based on academic levels. In addition, overall scores generally increased upon education (p<0.001). Therefore, the questionnaire is valid and reliable for assessing elderly caregivers' competencies in geriatric dermatology of which could be improved by education.